Information literacy in Nigerian higher institutions – any role for librarians? (2011)
It is the aim of this paper to mobilize Nigerians to view information illiteracy as an obstacle to progress in personal and social lives. The paper showed that information literacy is a major route to overcoming poverty, hunger and disease in the immediate environment. The paper finally examined strategies for combating information illiteracy like application of ICT and made recommendations on what Nigerian University libraries and librarians working in them should do/adopt to promote literacy awareness among Nigeria’s teeming population.